Kyrgyz Republic : Second Review Under the Three-Year Arrangement Under the Extended Credit Facility and Request for Modification of Performance Criteria: Staff Report; and Press Release. (IMF Staff Country Reports; Country Report ;, 2012)
This paper presents key findings of the Second Review for the Kyrgyz Republic under the Extended Credit Facility. Buoyant revenue collection and significant shortfalls in external financing led to a lower-than-programmed fiscal deficit for 2011. The overall health of the banking sector continued to improve but vulnerabilities remain. Strong adherence to the policies agreed under the IMF-supported program has played an important role in achieving economic recovery and macroeconomic stabilization. The fiscal stance for 2012 is appropriate and reflects pressing social and infrastructure development needs.